Providing organizations with a validated instrument for an Enterprise Service Management capability - Daria Goscinska; Till J. Winkler (Electronic Markets, 2024)
In light of new digital opportunities, enterprises require modernization also with regard to intra-organizational business and IT management. Enterprise Service Management (ESM) is an organizational capability aimed at a more efficient and effective IT and business service management in organizations. Although ESM has been recognized as an approach to improve customer and employee satisfaction and to create digital competitive advantage, there is a methodological and analytical void for organizations in how to measure their ESM capability. Motivated by this lack of measurability and tangibility, we aim to empirically validate the ESM capability model. Our contribution to this paper is empirical, as we provide a measurable instrument for further ESM studies. We aim to initiate a broader debate on ESM and thereby add to the scholarly establishment of the concept in the Information Systems and IT Management literature. Practically, we contribute by offering companies a validated and actionable set of ESM characteristics.
Keywords: M15; 620; Enterprise Service Management; Service systems; Empirical construct validation; Organizational transformation; PLS-SEM analysis